2019
DOI: 10.1038/s41467-019-10570-w
|View full text |Cite
|
Sign up to set email alerts
|

Ran promotes membrane targeting and stabilization of RhoA to orchestrate ovarian cancer cell invasion

Abstract: Ran is a nucleocytoplasmic shuttle protein that is involved in cell cycle regulation, nuclear-cytoplasmic transport, and cell transformation. Ran plays an important role in cancer cell survival and cancer progression. Here, we show that, in addition to the nucleocytoplasmic localization of Ran, this GTPase is specifically associated with the plasma membrane/ruffles of ovarian cancer cells. Ran depletion has a drastic effect on RhoA stability and inhibits RhoA localization to the plasma membrane/ruffles and Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 58 publications
(75 reference statements)
1
31
1
Order By: Relevance
“…Previous research has shown that altered expression of particular genes may affect ESCC cell metastasis, invasion, apoptosis and proliferation [15][16][17] . Our results agree with the fact that carcinoma cell metastasis and invasion are closely associated with abnormal cell adhesion, endodermal cell division and nuclear division [18][19][20] . Extracellular matrix (ECM), is a critical component of the cancer cell niche, it can provide the tissue with the mechanical support and also mediate the cell-microenvironment interactions 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that altered expression of particular genes may affect ESCC cell metastasis, invasion, apoptosis and proliferation [15][16][17] . Our results agree with the fact that carcinoma cell metastasis and invasion are closely associated with abnormal cell adhesion, endodermal cell division and nuclear division [18][19][20] . Extracellular matrix (ECM), is a critical component of the cancer cell niche, it can provide the tissue with the mechanical support and also mediate the cell-microenvironment interactions 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…The migration and invasion assays have shown that A375 hEVs but not nEVs induced invasion of A375 cells and NHDFs compared to A375 nEVs, while 501Mel hEVs increased invasion of NHDFs at early time points only. This could be due to the increased expression of PRMT5 in the melanoma hEVs, as PRMT5 well as RNA have recently been shown to regulate cancer cell invasion [72][73][74]. Here, we did not observe an effect of nEVs or hEVs on proliferation in normoxic conditions, whereas Patton et al have recently shown that hEVs derived from pancreatic cancer cells can promote proliferation, however under hypoxia [75].…”
Section: Discussioncontrasting
confidence: 75%
“…Ran can form a complex with RhoA, leading to RhoA stabilization and activation. This Ran-RhoA signaling complex could be a molecular target for controlling cancer metastasis [ 128 ].…”
Section: Functional Pathways Affected By Oc Fitness Genesmentioning
confidence: 99%